New host records of parasites in the Malayan red jungle fowl, Gallus gallus spadiceus - Lee, Chu Chong; Babjee, Shaik Mohamed Amin (Universiti Pertanian Malaysia Press, 1993)
Thirty species of parasites were recovered from seven adult male Malayan red jungle fowls Gallus gallus spadiceus from Ulu Langat, Selangor, Malaysia. Fifteen species of the parasites are newly recorded for this host; they are Pseudolynchia canariensis, Eimeria sp., Trichomonas gallinarum, Ascaridia galli, Capillaria annulata, Capillaria contorta, Cardiofilaria nilesi, Dispharynx spiralis, Gongylonema sp., Heterakis gallinarum, Tetrameres fissispina, Hymenolepis cantaniana, Raillietina cesticillus, Raillietina tetragona and Postharmostomum gallinum. The most common parasites are the nematode species of Heterakis and Capillaria.